2001
DOI: 10.1093/oxfordjournals.molbev.a003919
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Recent Population Expansion in the Evolutionary History of the Malaria Vectors Anopheles arabiensis and Anopheles gambiae

Abstract: Gene flow in malaria vectors is usually estimated based on differentiation indices (e.g., F(ST)) in order to predict the contemporary spread of genes such as those conferring resistance to insecticides. This approach is reliant on a number of assumptions, the most crucial, and the one most likely to be violated in these species, being mutation-migration-drift equilibrium. Tests of this assumption for the African malaria vectors Anopheles gambiae and Anopheles arabiensis are the focus of this study. We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 39 publications
9
122
0
Order By: Relevance
“…gambiae (Zheng et al 1996) and, with the exception of Ag2H197 (inversion 2Ra), were not contained within polymorphic inversions. Previous studies had found these markers to be highly variable and to amplify reliably (Donnelly et al 2001;Pinto et al 2002;Wondji et al 2002). None of these markers are within the ''genomic islands of speciation'' identified by other authors (Turner et al 2005) but some of the markers show marked differences in allele frequencies between molecular forms (Pinto et al 2002;Wondji et al 2002).…”
Section: Methodsmentioning
confidence: 88%
“…gambiae (Zheng et al 1996) and, with the exception of Ag2H197 (inversion 2Ra), were not contained within polymorphic inversions. Previous studies had found these markers to be highly variable and to amplify reliably (Donnelly et al 2001;Pinto et al 2002;Wondji et al 2002). None of these markers are within the ''genomic islands of speciation'' identified by other authors (Turner et al 2005) but some of the markers show marked differences in allele frequencies between molecular forms (Pinto et al 2002;Wondji et al 2002).…”
Section: Methodsmentioning
confidence: 88%
“…Recent expansions in a variety of disease vectors, such as Anophelinae (Donnelly et al, 2001;Dusfour et al, 2007;Matthews et al, 2007), and black flies (Pramual et al, 2005) appear to be tied to human population expansions and/or to climate changes and to the rise of agriculture, providing significant new breeding sites and sources of bloodmeals (Coluzzi, 1982). Coluzzi (1982) proposed that because these species were dependent on humans for feeding and breeding sites, populations may have mirrored the growth in populations of humans and domestic animals during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of partial sequence of mitochondrial DNA have shown that large numbers of haplotypes are shared between A. gambiae, A. arabiensis and A. bwambae Thelwell et al, 2000;Donnelly et al, 2001), but whether this is a result of introgression or retention of ancestral polymorphisms is unresolved Thelwell et al, 2000). In this study, we examine patterns of intra and interspecific differentiation in ways that can allow us to distinguish between contemporary introgression and retention of ancestral mitochondrial sequences.…”
Section: Introductionmentioning
confidence: 98%